LTE, LTE-advanced, and WiMAX : towards IMT-advanced networks - Hassanein, H. (Hossam).; Taha, Abd-Elhamid M.; Ali, Najah Abu. (Hoboken, N.J. : Wiley, 2012)
'This book will provide a concise introduction to both WiMAX and LTE, covering both interface and networking considerations. While there are many books which examine LTE or WiMAX there are few which compare the two technologies. While Parts I and II introduce and examine WiMAX and LTE respectively, Part III of this book will offer a multi-faceted comparison, carefully analyzing and distinguishing the characteristics of each technology and spanning both technical and economic merits. As well as offering a comparison between the two technologies, this book will provide a comprehensive description of each technology and its services at the practical and research level'--
'This book will provide a concise introduction to both WiMAX and LTE, covering both interface and networking considerations'--
Includes bibliographical references and index.
Keywords: Long-Term Evolution (Telecommunications); IEEE 802.16 (Standard)